Literasi Keuangan Pengusaha Tahu di Desa Kalikidang Kecamatan Sokaraja Kabupaten Banyumas - Cahyo Budi Santoso; Benny Krisbiantoro; Artika Wina Fitriani (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this activity is to improve the ability of tofu entrepreneurs to manage their business finances well, so that they can support the sustainability and development of tofu businesses in Kalikidang Village. The implementation methods used include socialization and financial management training, including recording transactions, preparing simple financial reports, and financial planning. The results of this activity show an increase in the understanding and skills of tofu entrepreneurs in managing their business finances. The impact of this service is increased efficiency and effectiveness in financial management of tofu businesses, which is expected to contribute to increasing income and welfare of entrepreneurs. The output obtained from this activity includes financial management training modules, activity reports, and documentation of training implementation. Thus, this PKM activity succeeded in making a positive contribution to the development of the tofu business in Kalikidang Village.